Caregiver burden, not patient cognitive impairment, predicts adherence to donepezil transdermal patch in Alzheimer's disease: A retrospective real-world study - Ryuji Yajima; Takanobu Ishiguro; Makoto Michikawa; Satoshi Naruse (Journal of Alzheimer's Disease Reports, 2026)
Background The donepezil transdermal patch is a useful option for Alzheimer's disease (AD) patients with poor oral adherence. However, treatment discontinuation due to skin irritation or management difficulties remains a clinical challenge. Objective To identify predictive factors for the successful continuation of the donepezil transdermal patch in a real-world setting. Methods A retrospective review included 26 AD patients newly prescribed or switched to the donepezil patch at a dementia center. Patients were divided into continuation (n = 15) and discontinuation (n = 11) groups based on a 12-week cutoff. We evaluated baseline demographics, Mini-Mental State Examination (MMSE), Clinical Dementia Rating-Sum of Boxes (CDR-SB), Alzheimer's Disease Assessment Scale-Cognitive Subscale for Activities of Daily Living (ADL-Cog), and caregiver burden using the 8-item Zarit Burden Interview (Zarit-8). Multivariate logistic regression identified risk factors for discontinuation. Results Univariate analysis showed no significant differences between groups in age (p = 0.855), MMSE (p = 0.677), CDR-SB (p = 0.762), and ADL-Cog (p = 0.826). Although the mean Zarit-8 score was higher in the discontinuation group (14.00 ± 10.70 versus 7.86 ± 5.55, p = 0.171), this lacked statistical significance. However, multivariate regression revealed a higher Zarit-8 score was a significant independent predictor of discontinuation after adjusting for age (p = 0.038, OR = 1.134). Conclusions Caregiver burden, rather than patient cognitive function or impairment in activities of daily living, significantly predicts discontinuation of the transdermal patch. To the best of our knowledge, no previous studies have utilized the Zarit burden scale as a clinical predictor of pharmacological adherence. Assessing caregiver reserve before introduction is crucial for maintaining adherence.